Reflecting Upon the Past? Development Studies' Ambivalent Relation to History. (April 2023) - Harwood, Jonathan
It has often been pointed out that development policy takes little notice of the history of development. Given the pressures under which policymakers have to operate, this is perhaps not altogether surprising. Occasionally, however, it is also suggested that Development Studies as a discipline also lacks a thorough-going appreciation of history. In view of the importance of historical perspective for any policy-relevant field, this claim deserves scrutiny. As a first step toward illuminating this issue, the article considers the ways in which development history is addressed in introductory textbooks used at British universities. It indicates that, with a few exceptions, texts' discussion of history is generally weak in several respects. By contrast, the research literature in Development Studies is blessed with a large number of historically well-informed works. The defects of the textbooks, therefore, cannot be attributed to a dearth of appropriate source material. Instead, it would appear that textbook authors are failing to draw upon the research literature. In concluding, the article explores the possibility that Development Studies, like other policy-relevant disciplines in the social sciences, may be characterized by distinct knowledge traditions which operate largely in isolation from one another.